Condom use among injection drug users accessing a supervised injecting facility. Issue 2 (23rd September 2008) - Marshall, B D L; Wood, E; Zhang, R; Tyndall, M W; Montaner, J S G; Kerr, T
Abstract : Objectives: Although supervised injecting facility (SIF) use has been associated with reductions in injection-related risk behaviours, the impact of SIFs on the sexual behaviour of injection drug users (IDUs) has not been thoroughly investigated. Therefore, we examined the patterns and predictors of condom use among SIF users in Vancouver, Canada. Methods: We performed a longitudinal analysis of the factors associated with consistent condom use among IDUs recruited from within a SIF. Results: Among 1090 individuals, 650 (59.6%) reported a sexual partner in the past 6 months at baseline. Consistent condom use was reported by 108 (25.3%) and 205 (61.6%) individuals reporting regular or casual partners, respectively. After 2 years of observation, these proportions increased to 32.9% and 69.8%, respectively. In multivariate analysis, predictors of consistent condom use with regular partners included HIV positivity (adjusted odds ratio (AOR) 2.23; 95% CI 1.51 to 3.31), injecting with a sex partner (AOR 0.50; 95% CI 0.37 to 0.68), enrollment in addiction treatment (AOR 0.68, 95% CI 0.52 to 0.89) and time since recruitment (AOR 1.29; 95% CI 1.06 to 1.55 per year). Predictors of consistent condom use with casual partners included HIV positivity (AOR 1.70; 95% CI 1.03 to 2.81), syringe borrowing (AOR 0.54; 95% CI 0.32 to 0.91) and syringe lending (AOR 0.52; 95% CI 0.32 to 0.84). Conclusions: Our results demonstrate that among SIF users, consistent condom use was more frequent among casual sex partners and among HIV positive individuals. Importantly, while the prevalence of consistent condom use was low at baseline, it increased over time. Our findings suggest a possible beneficial effect of the SIF on safer sexual practices.